Euro area production function and potential output: a supply side system approach - Alpo Willman (European Central Bank (ECB), 2002)
In this paper, we present a three equation supply-side model based on aggregation across sectors with sector specific mark-ups and the technology parameters of the production function. The model has been applied to euro area data from the 1970s assuming that the underlying production function is either CES or Cobb-Douglas. Estimation results support the Cobb-Douglas case and the estimated supply-side model accounts satisfactorily for the stylised features of the data, i.e. the hump shape in the labour income share coupled with the relatively stable capital-to-labour income ratio and a noticeable change in profit margins and sectoral production shares. We also produce estimates of potential output and the output gap conditional on estimated production functions and examine the sensitivity of output gap estimates with respect to the alternative parameterisation of the production function.
Keywords: E23; E25; 330